Is anemia an independent risk factor for postpartum depression in women who have a cesarean section? - A prospective observational study - Nirmala Chandrasekaran; Leanne R De Souza; Marcelo L Urquia; Beverley Young; Anne Mcleod; Rory Windrim; Howard Berger (BMC, 2018)
Abstract Background The symptoms of anemia and depression are very similar suggesting that there may be an association between the two entities. The aim of this study is to assess whether postpartum anemia (PPA) is an independent risk factor for de novo postpartum depression (PPD)in women undergoing elective cesarean section. Methods Women after an uncomplicated term cesarean section were recruited and their hemoglobin and iron status were measured on day 3-5 post section and again at 6 weeks. Postpartum depression was screened using the Edinburgh Postnatal Depression Scale (EPDS) and functional capacity was assessed with the RAND 12-item Health survey. Results One hundred and three women completed the study. The incidence of probable postpartum depression (PPD) as defined by EPDS score ≥ 10 was 17% at 6 weeks. There was no difference in hemoglobin or iron status in women who had PPD compared to those without (OR-0.69; 95% CI-0.15-2.49). Similarly, there was no significant association between low hemoglobin and maternal functional status (OR -1.03; 95% CI-0.34 - 2.94). Conclusions Neither anemia or low iron stores were found to be an independent risk factors for postpartum depression or decreased postpartum functional capacity in women who undergo an elective cesarean section.